Feasibility of Natural Salt-licks for Wildlife-Watching in Segaliud-Lokan Forest Reserve, Sandakan, Sabah - Lim Wing-Shen; Yip Pui-Mun; Andy Russel Mojiol; Collin Goh; Paul Liau; Liaw Yi-Chuang; Sanchez Vincent John (IOP Publishing, 2020)
Natural salt-licks are well-recognized as wildlife-watching hotspots that can provide visitors with high opportunities for sighting many different outstanding mammals at close-range. Various natural salt-licks were discovered throughout Segaliud-Lokan Forest Reserve (SLFR), but then the physical availability of local mammals at given licks were yet to be examined scientifically by past researchers. Henceforth, this study intended to investigate mammal species that were available for wildlife-viewing at the licks in SLFR. Four natural wet licks that were accessible from the main road and situated close to Sungai Rawog were selected as sampling areas to identify mammal species that visited given licks across different times through camera trapping survey. A total of 676 independent sightings of 12 different mammal species were recorded in 197 trap nights, especially at SL59 and during night-time. Sighted mammal individuals were mainly comprised of large-sized, threatened and non-carnivorous species, where Sambar Deer, Bearded Pig, Orang-utan, and Banteng were identified as the top 4 mammal species that were detected frequently at the licks in SLFR. In sum, it is feasible to conduct wildlife-viewing activity at the licks in SLFR, although further research is required to investigate the actual sighting probability and viewing duration of different mammal species by visitors at given licks and across different times or seasons.